2002
DOI: 10.1007/s10096-002-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Mycoplasma pneumoniae in Children with Acute Pharyngitis

Abstract: In order to define the role, the risk factors, and the clinical and laboratory characteristics of Mycoplasma pneumoniae infection in children with pharyngitis, 184 patients with acute non-streptococcal pharyngitis (102 males; median age, 5.33 years) were studied. Acute Mycoplasma pneumoniae infection was demonstrated in 44 (23.9%) patients. A history of recurrent episodes of pharyngitis (defined as at least 3 acute episodes of pharyngitis in the 6 months preceding enrollment) appeared to be the more useful par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
2
21
0
4
Order By: Relevance
“…Inflammation of the throat may be present, especially in children, with or without cervical adenopathy, and conjunctivitis and myringitis sometimes occur (7,125,152). Children under 5 years of age are most likely to manifest coryza and wheezing, and progression to pneumonia is relatively uncommon, whereas older children aged 5 to 15 years are more likely to develop bronchopneumonia, involving one or more lobes, sometimes requiring hospitalization (137,273,392).…”
Section: Vol 17 2004 M Pneumoniae As a Human Pathogen 707mentioning
confidence: 99%
“…Inflammation of the throat may be present, especially in children, with or without cervical adenopathy, and conjunctivitis and myringitis sometimes occur (7,125,152). Children under 5 years of age are most likely to manifest coryza and wheezing, and progression to pneumonia is relatively uncommon, whereas older children aged 5 to 15 years are more likely to develop bronchopneumonia, involving one or more lobes, sometimes requiring hospitalization (137,273,392).…”
Section: Vol 17 2004 M Pneumoniae As a Human Pathogen 707mentioning
confidence: 99%
“…It has recently been demonstrated that a significant part of non-streptococcal acute pharyngitis may be associated with Mycoplasma pneumoniae and/or Chlamydia pneumoniae infection, but it has not been established whether these atypical bacteria act simply as co-pathogens or as primary aetiological agents, nor is it known what the outcome of such infections is when they are not treated with antibiotics Esposito et al, 2002b). Definition of the real role of M. pneumoniae and C. pneumoniae in causing acute pharyngitis would be useful for deciding the best diagnostic and therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…11 years) without any history of respiratory tract infection or antibiotic treatment in the 3 months before enrolment, who were seen for minor surgical problems, were enrolled as a control group. The study protocol was approved by the institutional review board of the University of Milan and written informed consent was obtained from the parents or legal guardians of all participants.Upon enrolment, systematic recordings were made of the children's demographic characteristics and medical history by using standardized written questionnaires Esposito et al, 2002b). Questions included duration of breast-feeding, living conditions, childcare attendance, number and age of family members, birth rank, smoking habits of family members living together, number and type of respiratory infections in the previous 6 months, presence of a history of recurrent pharyngitis (defined as at least three acute episodes in the 6 months preceding enrolment) (Korppi, 1997;Esposito et al, 2002b) and number and type of antimicrobials administered during the previous 6 months.…”
mentioning
confidence: 99%
“…Mycoplasma pneumoniae is a common respiratory bacterial pathogen that affects both the upper and lower respiratory tracts of children and adults (1)(2)(3)(4)(5)(6)(7)(8)(9). More recent data demonstrate an association between M. pneumoniae respiratory infection and reactive airway disease and asthma (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%